Interplay between mechanical and electronic degrees of freedom in π-stacked molecular junctions: From single molecules to mesoscopic nanoparticle networks - Ghane, Tahereh; Nozaki, Daijiro; Dianat, Arezoo; Vladyka, Anton; Gutierrez, Rafael; Chinta, Jugun Prakash; Yitzchaik, Shlomo; Calame, Michel; Cuniberti, Gianaurelio (Giovanni) (Journal of Physical Chemistry C, 2015)
Functionalized nanoparticle networks offer a model system for the study of charge transport in low-dimensional systems as well as a potential platform to implement and test electronic functionalities. The electrical response of a nanoparticle network is expected to sensitively depend on the molecular interconnects, i.e., on the linker chemistry. If these linkers have complex charge transport properties, then phenomenological models addressing the large-scale properties of the network need to be complemented with microscopic calculations of the network building blocks. In this study we focus on the interplay between conformational fluctuations and electronic π-stacking in single-molecule junctions and use the obtained microscopic information on their electrical transport properties to parametrize transition rates describing charge diffusion in mesoscopic nanoparticle networks. Our results point out the strong influence of mechanical degrees of freedom on the electronic transport signatures of the studied molecules. This is then reflected in the varying charge diffusion at the network level. The modeling studies are complemented with first charge transport measurements at the single-molecule level of π-stacked molecular dimers using state-of-the-art mechanically controllable break junction techniques in a liquid environment.
CRIS-Team Scopus Importer:2023-03-20